Ergometry for estimation of mechanical power output in sprinting in humans using a newly developed self-driven treadmill - Funato, K.; Yanagiya, T.; Fukunaga, T. (European Journal of Applied Physiology, 2001)
An evaluation of mechanical power during walking and running in humans was undertaken after developing a specially designed running ergometer (RE) in which the subjects gripped the handlebar in front of them keeping both arms straight and in a horizontal position. Ten subjects participated in comparisons of the mean horizontal pushing force (MFam) on the handlebar with the mean horizontal ground reaction force (MFfp) recorded by force platform under the RE during five different constant speeds of walking or running and sprint running with maximal effort. Mechanical power developed during sprint running on the RE was compared with a 50 m sprint. Mean linear velocity (Mv) of the RE belt was recorded by the rotary encoder attached to the axis of the belt. Mean mechanical power calculated from the handlebar setting (MPam=MFam × Mv) was compared to that calculated from force platform recordings (MPfp=MFfp × Mv). A high test-retest reproducibility was observed for both MFfp (r=0.889) and MFam (r=0.783). Larger values for the coefficient of variation for MFam (11.3%-15.8%) were observed than for MFfp (3.3%-8.2%). The MPam, which were obtained from five different constant speeds of walking, running and sprint running were closely correlated to those of MPfp (y=0.98x - 19.10,r=0.982, P < 0.001). In sprint running, MPam was 521.7 W (7.67 W · kg-1) and was correlated to the 50 m sprint time (r=-0.683, P < 0.01). It is concluded that the newly developed RE was useful in the estimation of mechanical power output during human locomotion such as when walking, jogging and sprinting.